Applicability of nutrition assessment methodologies in post-disaster situations in five typhoon affected Philippine provinces. - Talavera, M. T. M.; Tuazon, M. A. G.; Felix, A. dR.; Gordoncillo, N. P.; Narciso, M. H.; Bustos, A. R.; De Juras, A. R.; Padilla, L. M. (2003)
This study assessed the applicability of the different nutrition assessment methodologies namely, anthropometry, clinical assessment, focus group discussion, and key informant interview in five disaster affected provinces in the Bicol and MIMAROPA regions. It also described the nutrition situation and generated implications on the use of these methodologies as inputs in the development of a protocol for rapid nutrition assessment in post-disaster situations. Results showed that undernutrition was found to be a problem among preschool and older children, adults, and the elderly. Common illnesses such as fever, cold, and coughs were also observed including signs suggestive of micronutrient malnutrition. Results of the focus group discussion and key informant interviewers showed that the primary causes on undernutrition are inadequate food intake and poor health status. The study recommends the use of mid-upper arm circumference measurements, weighing using calibrated bathroom scale, clinical assessment, and key informant interviewers as methodologies for inclusion in the protocol for rapid nutritional assessment.
Keywords: Nutritional assessment; Disaster victims